[Atlanto-occipital dislocation-A challenge with respect to making the diagnosis and treatment]. - Gelse, Kolja; Guggenberger, Matthias (Die Unfallchirurgie, 2024)
BACKGROUND: The correct diagnosis and treatment of the atlanto-occipital dislocation (AOD) remains a major challenge. OBJECTIVE: To evaluate the different radiological diagnostic criteria for AOD and discuss potential treatment strategies based on a case with AOD and additional fracture of the atlas. MATERIAL AND METHODS: A 29-year-old male patient is presented who suffered from AOD with concomitant fracture of the anterior and posterior arches of the atlas with rotational atlantoaxial dislocation following an accident in forestry. The following parameters were evaluated for the diagnosis and assessment of postoperative reduction: Powers ratio, the X‑lines-method, Wackenheim line, basion-dens interval (BDI), basion-axial interval (BAI) and occipital condyle-C1 interval (CCI). RESULTS: Stabilization was performed by occipitocervical spondylodesis from C0 to C2/3. For final reduction it was necessary to reduce the malrotation of the atlas. In the presented case, the revised CCI proved to be a sensitive and valid yet practical parameter. Powers' ratio and the BDI were less suited for assessing the diagnosis. The X‑lines-method, Wackenheim line and the BAI did not adequately detect the pathological situation. DISCUSSION: The AOD is a severe injury requiring immediate correct diagnosis for later adequate treatment results. Among the published parameters, the revised CCI proved to be a practical and valid parameter to detect AOD. For definitive treatment, the operative occipitocervical stabilization is regarded as the method of choice.
EVALuna2:595775